A213 VIDEO EDUCATIONAL MATERIAL FOR PATIENTS PREPARING FOR COLONOSCOPY - Garber, J E (J Can Assoc Gastroenterol, 2019)
BACKGROUND: Preferences for receipt of information vary among individuals, with many patients showing an interest in receiving via video content. Although several educational videos on colonoscopy are available, most of them have not been evaluated systematically. AIMS: To develop and compare a colonoscopy video educational resource to a previous video on similar subject matter. METHODS: We developed a new video resource, based on feedback from patients and health care providers and recommended content in literature. A similar content video from the web was identified as the most highly rated by an advisory group. Individuals attending gastroenterology clinics, blinded to the source of videos, were recruited to watch both the New Video and the Similar Video. The order of watching the videos was randomly assigned to allow the assessment of order effects. After watching, participants were asked to rate each video based on: amount of information, clarity, trustworthiness, ease of watching/understandability, familiarity, reassurance, information learned, understanding from the patient’s point of view, appeal, and if they would recommend the video. Participants were then asked which video they preferred and why they preferred it based on clarity, trustworthiness, ease of watching/understandability, and reassurance. Participants were also asked to explain what they liked/disliked about the videos and if they had any suggestions for improving the material. RESULTS: 232 participants viewed both videos. When the New Video was viewed first 64% preferred the New Video and 31% preferred the Similar Video. When the Similar Video was viewed first 78% preferred the New Video and 20% preferred the Similar Video. Of the participants that had not had a previous colonoscopy, 66% preferred the New Video, while 74% of the participants with previous colonoscopy experience preferred the New Video. Multivariable logistic regression analysis also suggested that participants prefer the New Video if they saw it second. Participants rated the New Video as clearer and more trustworthy than the Similar Video. Many participants specified in the open-ended questions they liked New Video better because it was clearer, it was more informative, and was more visually appealing. CONCLUSIONS: We have developed and validated a new colonoscopy video educational material, which is freely available on the web. Our study suggests that in information evaluation studies, it is important to consider order effects. We have developed a process to appraise and compare different video information materials against each other. FUNDING AGENCIES: None